Growth and Nutrition in Pediatric Chronic Kidney Disease - Silverstein, Douglas M. (Frontiers in Pediatrics, 2018)
Children with chronic kidney disease (CKD) feature significant challenges to the maintenance of adequate nutrition and linear growth. Moreover, the impaired nutritional state contributes directly to poor growth. Therefore, it is necessary to consider nutritional status in the assessment of etiology and treatment of sub-optimal linear growth. The major causes of poor linear growth including dysregulation of the growth hormone/insulin-like growth factor-I (IGF-I) axis, nutritional deficiency, metabolic acidosis, anemia, renal osteodystrophy/bone mineral disease, and inflammation. This review summarizes the causes and assessment tools of growth and nutrition while providing a summary of state of the art therapies for these co-morbidities of pediatric CKD.